Влияние осесимметричных несовершенств на частоты колебаний нагруженных ребристых оболочек - Гавриленко, Г.Д.; Мацнер, В.И. (Видавничий дім "Академперіодика" НАН України, 2008)
A new approach to the problem of cylindrical shell vibrations is used for the estimation of oscillation frequencies of shells with initial local axisymmetric deflection. The analytic solutions and the results of calculation are presented.